Pengaruh Pemasaran Digital Terhadap Perilaku Konsumen - Hendrik Trymedia Laoli; William Zebua (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the impact of digital marketing on consumer behavior in the e-commerce context. Using data from major e-commerce platforms in Indonesia, we examined how various digital marketing strategies influence purchasing decisions, consumer engagement, and brand loyalty. The research employed quantitative analysis of consumer behavior data from 2023, including purchase patterns, response to digital advertisements, and social media engagement. Results indicate that personalized marketing campaigns increased purchase probability by 45%, while social media integration led to 30% higher customer engagement rates. Mobile-based marketing showed particular effectiveness, with 60% of purchases initiated through mobile devices. The study concludes that digital marketing significantly influences modern consumer behavior, particularly in areas of purchase decision-making and brand interaction. These findings provide valuable insights for businesses adapting to digital transformation in the retail sector.